2018
DOI: 10.1111/1756-185x.13372
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody profile in children with Kawasaki disease on long‐term follow‐up: A prospective study from North India

Abstract: These autoantibodies likely develop in children with KD during the acute stage and may persist for many years. There is no concrete evidence to suggest that these children are at increased risk of developing an autoimmune disease in the future. However, there is some justification for prolonged surveillance for development of autoimmune manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…KD is a multi-systemic disease with varied clinical manifestations [2,3,14]. It predominately affects pre-school children.…”
Section: Discussionmentioning
confidence: 99%
“…KD is a multi-systemic disease with varied clinical manifestations [2,3,14]. It predominately affects pre-school children.…”
Section: Discussionmentioning
confidence: 99%
“…The latest researches demonstrated that CD138+ plasma cells in bone marrow were inclusive of a group of long-lived plasma cells, which present a memory nature through persistent secretion of specific antibodies even though the patients had not exposed to the pathogens for decades [4648]. Hence, it can be speculated that those increased CD138+ ASCs may be an explanation for the low recurrent rate of KD, as well as for the self-antibodies lasting for years [49].…”
Section: Discussionmentioning
confidence: 99%
“…One hundred KD patients with or without coronary artery dilatation showed more subclinical abnormalities of left ventricular function than healthy controls in children more than 7 years after KD (8). Autoantibodies, a target for long-term assessment, were found to last for a long time in children with KD (9). Lipid profile abnormalities in KD were found to persist for 1 year in a cohort study with 27 children (10).…”
Section: Introductionmentioning
confidence: 97%